PENGARUH KEPERCAYAAN DIRI SISWA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPA PADA SISWA - Sani, Tiara; Mustika, Dea (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The purpose of this study was to determine the Influence of Student Self-Confidence and Learning Motivation on Science Learning Outcomes in Grade V Students. From the results of the pre-research, it is known that the learning motivation and self-confidence of Grade V students are still lacking. This can be seen when science learning takes place. This study uses a quantitative writing type. The method used is a survey method with a correlational approach. The data sources in this study are primary data (questionnaire results) and secondary (documentation). The research instrument used is a questionnaire that is tested through 2 tests, namely validity and reliability tests. While for the analysis of the data obtained, testing will also be carried out. Namely the normality test, homogeneity, linearity, multiple regression equations and hypothesis tests. The results and discussion of the findings can be concluded that: There is an influence of learning interest on the science learning outcomes of Grade V students.